Asbab Al-Nuzul as Historical Criticism on The Emergence of Revisionist Islam - Mahbub Ghozali (Buletin Al-Turas, 2020)
This study was aimed to construct early of Islamic history by using sources of asbab al-nuzul. The use of the history of asbab al-nuzul was expected to provide a critique of the revisionist’s view of the early of Islam. This study used two methods, the historical critical method and hermeneutics. Data on in this study focused on asbab al-nuzul al-Qur’an by al-Wahidi. The study concluded that the asbab al-nuzul, which seen as an exegesis device, basically was a historical device that provided historical narrative and context in the early days of Islam. Because of this, asbab al-nuzul was used by many commentators as a tool for understanding the Qur’an. This research found that Islam emerged in Hijaz with a number of narratives asbab al-nuzul that mentioned. Likewise, it was found the intersection of Islam with other religions indicated that Islam was not exclusive and was not a continuation of these religions. Islam was present in a mulitireligious society. Islam existed to restore the deviation of worship performed by the majority of the Arab. The criteria required in the asbab al-nuzul could be considered valid because they could fulfil the historical assumptions set by the revisionists.